Studi Komparatif Antara Penambahan Efective Microorganism-4 (EM-4) dan Limbah Lumpur Aktif Sebagai Stimulator dalam Pembuatan Kompos di RSUP Dr. Sardjito Yogyakarta - ASYFIRADAYATI, REZANIA (2011)
The efforts to handling amount of litter is to process the litter become compost. EM-4 and activated sludge waste of Dr. Sardjito General Hospital are stimulators useful to accelerate composting process. Purpose of this research was to know the difference of time, pH, temperature and NPK content of compost with addition of EM-4 and activated sludge waste. Method of this research was experiment with posttest only with control group design. Population of this research were all leaf litters taken from park of Dr. Sardjito General Hospital everyday weighting of 40 kg litters, sample of the research were 27 kg litters 3 kg of the litters were assigned into every control group, 3 kg are assigned into EM-4 treatment and 3 kg are assigned into active sludge waste and every experiment was repeated 3 times. Statistical test used in this research is One-way ANOVA assisted by SPSS 17 software. Result of the research indicated that there were differences of time and temperature but there was no difference pH between compost added with EM- 4 and one added with activated sludge waste and whereas there was a significant difference NPK content between EM-4-added compost and activated sludge waste-added compost. Results of laboratory test on EM-4-added compost indicated average content of N (1.17%), P (0.127%), and K (0.79%). Whereas on activated sludge waste-added compost contained average content of N (2.28%), P (0.217%) and K (1.993%).